Integration of speech and gesture in aphasia. Issue 3 (7th February 2018) - Cocks, Naomi; Byrne, Suzanne; Pritchard, Madeleine; Morgan, Gary; Dipper, Lucy
Abstract: Background: Information from speech and gesture is often integrated to comprehend a message. This integration process requires the appropriate allocation of cognitive resources to both the gesture and speech modalities. People with aphasia are likely to find integration of gesture and speech difficult. This is due to a reduction in cognitive resources, a difficulty with resource allocation or a combination of the two. Despite it being likely that people who have aphasia will have difficulty with integration, empirical evidence describing this difficulty is limited. Such a difficulty was found in a single case study by Cocks et al . in 2009, and is replicated here with a greater number of participants. Aims: To determine whether individuals with aphasia have difficulties understanding messages in which they have to integrate speech and gesture. Methods & Procedures: Thirty‐one participants with aphasia (PWA) and 30 control participants watched videos of an actor communicating a message in three different conditions: verbal only, gesture only, and verbal and gesture message combined. The message related to an action in which the name of the action (e.g., 'eat') was provided verbally and the manner of the action (e.g., hands in a position as though eating a burger) was provided gesturally. Participants then selected a picture that 'best matched' the message conveyed from a choice of four pictures which represented a gesture match only (G match), a verbal match only (V match), an integrated verbal–gesture match (Target) and an unrelated foil (UR). To determine the gain that participants obtained from integrating gesture and speech, a measure of multimodal gain (MMG) was calculated. Outcomes & Results: The PWA were less able to integrate gesture and speech than the control participants and had significantly lower MMG scores. When the PWA had difficulty integrating, they more frequently selected the verbal match. Conclusions & Implications: The findings suggest that people with aphasia can have difficulty integrating speech and gesture in order to obtain meaning. Therefore, when encouraging communication partners to use gesture alongside language when communicating with people with aphasia, education regarding the types of gestures that would facilitate understanding is recommended.